Determination of Antioxidant Properties of Ethanol and Water Extracts of Achillea millefolium L. (Yarrow) - Keser, Serhat; Celik, Sait; Turkoglu, Semra; Yilmaz, Okkes; Turkoglu, Ismail (Asian Journal of Chemistry, 2011)
Achillea millefolium L. is a member of the Asteraceae family that is commonly referred to as ‘yarrow’ and has been used in folk medicine against several disturbances including skin inflammations, spasmodic and gastrointestinal disorders, as well as hepato-biliary complaints. Ethanol and water extracts were prepared from powdered A. millefolium flowers, leaves and seeds. In this study, antioxidant properties were studied by 2,2-azino-bis(3-ethylbenzthiazoline-6- sulfonic acid) (ABTS•+) radical scavenging, 1,1-diphenyl-2-picryl-hydrazyl free radical (DPPH•) scavenging, superoxide anion (O2 •−) radical scavenging, reducing activity and ferrous metal chelating activity assays. In conclusion, A. millefolium flowers, leaves and seeds had effective ABTS•+ and DPPH• radical scavenging, superoxide anion radical scavenging, reducing power and metal chelating activities. Additionally, these various antioxidant activities were compared with BHA, BHT and α-tocopherol as reference antioxidants.